CME: Continuing Medical Education Questions: June 2018. (June 2018) - Ho, Edith Y.
Abstract : N/A: To receive CME/MOC credit for this activity, please go to: http://acgjournalcme.gi.org/ Article Title: The Gastroenterologist's Guide to Management of the Post Liver Transplant Patient